Behavioral and Cellular Tagging in Young and in Early Cognitive Aging - Gros, Alexandra; Lim, Amos W. H.; Hohendorf, Victoria; White, Nicole; Eckert, Michael; McHugh, Thomas John; Wang, Szu-Han (Frontiers in Aging Neuroscience, 2022)
The ability to maintain relevant information on a daily basis is negatively impacted by aging. However, the neuronal mechanism manifesting memory persistence in young animals and memory decline in early aging is not fully understood. A novel event, when introduced around encoding of an everyday memory task, can facilitate memory persistence in young age, but not in early aging. Here we investigated in male rats how sub-regions of the hippocampus are involved in memory representation in behavioral tagging and how early aging affects such representation, by combining behavioral training in appetitive delayed-matching-to-place task with the ‘cellular compartment analysis of temporal activity by fluorescence in situ hybridization’ technique. We show that neuronal assemblies activated by memory encoding were also partially activated by novelty, particularly in the distal CA1 and proximal CA3 subregions in young male rats. In early aging, both encoding- and novelty-triggered neuronal populations were significantly reduced, with a more profound effect in encoding neurons. Thus, memory persistence through novelty-facilitation engages overlapping hippocampal assemblies as a key cellular signature and cognitive aging is associated with underlying reduction in neuronal activation.